Does SUNN-SYMRK Crosstalk occur in Medicago truncatula for regulating nodule organogenesis? - Saha, Sudip (Plant Signal Behav, 2015)
Recently we reported that overexpression of intracellular kinase domain of Symbiosis Receptor Kinase (SYMRK-kd) hyperactivated spontaneous nodulation in Medicago truncatula indicating the importance of SYMRK ectodomain in restricting nodule number. To clarify whether sunn and sickle pathways were overcome by SYMRK-kd for hyperactivation of nodule organogenesis, we overexpressed SYMRK-kd in these mutants and analyzed for spontaneous nodulation in absence of rhizobia. Spontaneous nodulation in skl/SYMRK-kd roots was 2-fold higher than A17/SYMRK-kd roots indicating nodule organogenesis induced by SYMRK-k(d) to be ethylene sensitive. Intriguingly, sunn/SYMRK-kd roots failed to generate any spontaneous nodule which directly indicate the LRR-RLK SUNN to have a role in SYMRK-k(d) mediated nodule development under non-symbiotic conditions. We hypothesize a crosstalk between SUNN and SYMRK receptors for activation as well as restriction of nodule development.